Kegagalan Akuntabilitas Hibrida Dalam Program Makan Bergizi Gratis (MBG): Analisis Hukum, Tata Kelola, dan Risiko Keuangan Negara Dalam Pola Bantuan Pemerintah Berbasis Yayasan - Ahmad Zakiyuddin; Firman Alamsyah Taufik Robbi; Dina (Trasearch (Training, Research and Academy Society, 2026)
The Free Nutritious Meals Program (Makan Bergizi Gratis—MBG) is a strategic government policy designed to fulfil the public’s right to adequate nutrition through the Government Assistance (Bantuan Pemerintah—Banper) scheme. Its implementation, however, has produced a hybrid governance arrangement in which foundations serve as the formal recipients of government assistance, while operational control and actual decision-making authority are exercised by civil servants assigned to the Nutrition Fulfilment Service Units (Satuan Pelayanan Pemenuhan Gizi—SPPG) under the National Nutrition Agency (Badan Gizi Nasional—BGN). This study examines the disjunction between formal accountability and effective control from the perspectives of administrative law, public finance law, and public-sector risk management. It employs a normative juridical method using statutory, conceptual, and risk-governance approaches based on the 2017 COSO Enterprise Risk Management framework. The findings reveal a formal beneficiary–factual controller dichotomy that creates an accountability gap, increases the potential for maladministration and conflicts of interest, and exposes the state to financial losses. The concentration of procurement, payment, verification, and reporting functions in the hands of the factual controller further heightens the risk of public-sector fraud. This article proposes the Hybrid Accountability Failure Model, which argues that public accountability should follow effective control and decision-making authority rather than merely formal legal status. This governance structure also undermines the principles of transparency, accountability, effectiveness, and public participation. The study recommends a clear segregation of duties, written delegation of authority, the digitalisation of audit trails, and risk-based oversight. These findings contribute to the study of public governance, political accountability, and corruption-risk mitigation in partnership-based social welfare programmes.